Assessment of the knowledge, attitude and practice towards palliative care amongst the 4th year nursing degree students at Windhoek Campus, University of Namibia - Shigwedha, Nive N.; Amakali-Nauiseb, Taimi; Runone, Kalista (International Journal Of Community Medicine And Public Health, 2022)
Background: Nursing students who will be future nurses should have adequate palliative care knowledge, positive attitude and good practices. In Namibia, the nursing students’ knowledge, attitude and practice regarding palliative care remain unknown. This study was aimed at assessing the knowledge, attitude and practices towards palliative care amongst the 4th year nursing degree students at Windhoek Campus, University of Namibia. Methods: A cross-sectional survey using a quantitative approach with self-administered questionnaire as a tool for data collection was utilised among 83 nursing degree students. A simple random sampling technique was used in selecting the participants and a response rate of 98.7% (n=82) was achieved. Results: Showed the following: knowledge towards palliative care is suboptimal as only 54.9% (45) participant had good knowledge towards palliative care, while 45.1% (37) participants had poor knowledge on palliative care. Practice towards palliative care was good as 91.5% (75) participants had good practice towards palliative care, whilst 8.5% (7) participants bad practice. The overall level of attitude shows positive attitude amongst participants as 76.8% (63) had positive attitude towards palliative care, while 23.2% (19) had negative attitude. Conclusions: Integrating palliative care education is required as a pillar to improve student’s knowledge where the nursing educators are not only designing proper teaching content but also, they are using various teaching strategies to promote active and experimental learning regarding palliative care.